Application of Murabahah Operations on Gold Savings Products on Customer Deposit Fund Profits at Bank Syariah Indonesia (Case Study at Bank Syariah Indonesia Panyabungan Branch Office) - Pulungan, Rahmad; Syakir, Ahmad; Anggraimi, Tuti (Manunggal Halim Jaya, 2025)
This study aims to determine the